MEMAHAMI STUDI DOKUMEN DALAM PENELITIAN KUALITATIF - Nilamsari, Natalina (Universitas Prof. Dr. Moestopo (Beragama), 2014)
Qualitative research is a method of research used to uncover the problems in working life government organizations,private sector, civil society, youth, women, sports, arts and culture, and others that can be used as a policyfor the sake of the common welfare. Calls